PENGARUH KARAKTERISTIK PERUSAHAAN DAN ATRIBUT DEWAN KOMISARIS TERHADAP KEBIJAKAN DIVIDEN KAS - Christine Lini Patiran (Parsimonia - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to prove the effect of liquidity, free cash flow, leverage, company growth, the independent board of commissioners and the gender board of commissioners on cash dividend policy. This type of research is quantitative research with a causality approach. The sample of this research is non-financial companies that distribute dividends listed on the Indonesia Stock Exchange (BEI) in 2015-2019 with a total sample of 70 companies. The data used in this study are quantitative data, namely numbers in financial reports and annual reports obtained from secondary data sources, namely the website of the Indonesia Stock Exchange (IDX) and the websites of each public company. The data analysis method used is panel data regression analysis using Eviews 10 software. The results of this study indicate that company growth has a negative effect on cash dividend policy. Meanwhile, liquidity, free cash flow, leverage, independent board of commissioners and board of commissioners gender had no effect on cash dividend policy.